THE POTENTIAL OF BADONG MUSIC IN THE RAMBU SOLO' CEREMONY AS A THERAPEUTIC MEDIUM - Dwi Berkat Julia Rando; Nanang Erma Gunawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The study aims to explore the function of Badong traditional music performed in the traditional death ceremony of Rambu solo’ as a therapeutic medium. Badong music, which is rich in spiritual and social values, is believed to play a therapeutic role in aiding the emotional healing process of grieving families. This study examines how Badong musical elements, such as melody, rhythm, and lyrics, interact with cultural and spiritual values to support psychological recovery and social solidarity during the grieving process. This study employed a qualitative approach and utilized a ethnographic method. The research was conducted in Tana Toraja, especially in the Ulusalu area, which was known to be active in carrying out the Rambu solo’ ceremony. The primary data sources came from grieving families, Pa’Badong (ritual leaders), traditional leaders, and academics. Data collection techniques included participatory observation, in-depth interviews, and document analysis. The validity of the data was ensured through triangulation techniques, including source triangulation, methodological triangulation, and theoretical triangulation, by comparing data from various subjekts, data collection methods, and theoretical perspectives. The results of the study show that Badong music has a significant contribution in channeling emotions and supporting the emotional healing process for bereaved individuals. Slow, repetitive melodies, meaningful lyrics, and collective performance forms in ritual circles create a space of catharsis, strengthening spiritual and social attachments. This study concludes.